f(0) = 0, f(1) = 2, f''(0) = 0, f'(1) = 4.
let the polynomial be
Now
f(0) = 0
so d = 0
so polynomial reduces to
f(1) = 2,
a + b + c = 2
f''(0) = 0,
so b = 0
f'(1) = 4.
so 3a + 2b = 4
solving we get
a = 4/3
b = 0
c = 2/3
d= 0
so polynomial is
Is there a way to solve it using polynomial interpolation or something? I started out doing it the way you did it but, figured it was wrong since we were supposed to be learning about interpolation. I'll try to solve the other questions using that method for now. Thanks.